Penerapan Model Problem Based Learning untuk Meningkatkan Motivasi dan Hasil Belajar IPAS Berbantu Media Wordwall - Ira Monika; Subhanadri Subhanadri; Aprizan Aprizan (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2025)
The background of this research is the low motivation and learning achievement in the subject of Natural and Social Sciences (IPAS) at the elementary school level. The Problem Based Learning (PBL) model, which emphasizes contextual problem-solving and active student engagement, when combined with the interactive Wordwall media, is expected to encourage students to be more enthusiastic and actively involved in the learning process. This study aimed to improve students’ motivation and learning outcomes through the implementation of the PBL model assisted by Wordwall media. The research method employed was Classroom Action Research (CAR) conducted in two cycles. Data were collected through observation, questionnaires, tests, and documentation. The results showed an increase in learning motivation from the “good” category (75%) in the first cycle to the “very good” category (94%) in the second cycle, as well as an improvement in learning achievement from 66% (“fair” category) to 95% (“very good” category). The conclusion of this study is proven effective in enhancing students’ motivation, learning achievement, and the quality of the learning process. Future research may explore the application of this strategy in other subjects or educational levels to broaden its benefits and effectiveness.